Televisão; Indústria da música; Reality show musical no Brasil - Silva, Heitor da Luz (2013)
The thesis aims to address the relationship between television and the music industry in Brazil from an object little explored: the musical reality show. In order to analyze culturally the production strategies of all these television programs as an important current phenomenon of mass media now changing due to digital media, the qualitative research encompassed formats locally produced and exhibited in its first ten years of existence. The production of data for the analysis took place from a diverse collection of sources like: a) fragments and full episodes of the programs available on Youtube or collected directly by recording video from TV exhibitions, b) reports and critical reviews on newspapers and magazines that generate information and reflections about the programs and the participants, in particular those who gained prominence for its subsequent insertion into the music market, c) sites, official or not, about those TV shows and news releases to the media; d) interviews available in newspapers, magazines and the Internet with participants and those responsible for their production, as well as their jury. The analysis of these data enabled the postulation of the thesis that musical reality show was born as a set of television shows in which there is a protagonism of the music industry, but its trajectory as a subgenre over ten years in Brazilian TV make´s one note that a tension, articulated directly to that original feature, acquires its relevance and comes to define their function. This tension stems from moments of major and minor approach of the television subgenre s to the music industry in the modes of operation of TV shows taking into consideration mainly two axes: a) from the standpoint of economic rationality, in relation to the effort of direct transformation of participants in the great exponents of the music market, b) from the symbolic point of view, with the exposure of selection and operation modes of the industry mediated by cultural values involving genre and performance notions on the evaluations of the participants' presentations.